Influence of power step on the behavior of an Open Natural Circulation Loop as applied to a Parabolic Trough Collector. (January 2022) - Jinshah, B.S.; Balasubramanian, K.R.; Kottala, Ravikumar; Divakar, S.
Abstract: This paper investigates the dynamic behaviour of a low pressure open natural circulation loop applied to a parabolic trough collector. An in-house experimental setup is developed to perform the test. The experiments are performed on two distinct modes: H-mode and S-mode, corresponding to single-phase and two-phase flow. Three distinct power amplitude modes viz, 250, 325, and 464.3 W with a power step number of 24, 18 and 12 having a duration of 15, 20 and 30 min are considered. A Fast Fourier Transform analysis revealed that the flow in the loops is stable with a maximum decay ratio of 0.726. Instabilities, including Density Wave Oscillation, geysering and flashing, are observed during the test. Moreover, the thermal inertia of the loop has a significant role in the initial stage of power steps. An increase in the power step size conferred a 9.1%–33.4% increase in the outlet temperature of water in H-mode. In S-mode, an increase in power step size delayed the onset of boiling and reduced the duration of boiling by 2.8–14.32% and 8.03–22.02%. The loop can generate a mass flux of 40–42.5 kgm 2 s −1 in H-mode and up to 400 kgm 2 s −1 in S-mode, which is significant. Highlights: A parabolic trough collector base on an Open natural circulation loop is introduced. The effect of power step size and duration on the flow is examined in-house. Tests are performed on two different modes, namely hot water and steam generation modes. Thermal Oscillation and Type-I instabilities are noted with decay ratio of 0.726. Increased temperature, a delayed onset and reduced boiling duration is conferred.